Análise do processo interno de comunicação em um campus avançado de uma universidade federal - Baldance, Fernando Henrique Martins (2017)
The communication process has always played a major role in the development of humanity, ranging from rock paintings in prehistory, through the emergence of speech, writing, radio, television, evolving to the present day, where New information and communication technologies stand out for their undeniable ability to optimize communicative processes. The contemporary dynamism of people and organizations demands more and more attention with communication in order to guarantee the agility and quality of this process, but, faced with the inherent complexity of modern organizations, it is not always possible to offer these two characteristics simultaneously. Therefore, the objective of this work is to evaluate the quality of communication in the advanced campus of Varginha of the Federal University of Alfenas, searching, through questionnaires applied to undergraduate students, administrative technicians, outsourced employees and teachers, identifying characteristics and possible flaws that can be explored in order to propose improvements in the communicative process in order to make the institution more effective in this regard. The obtained data were analyzed in a globalized and segmented way in order to look for better ways to understand the behavior of the groups that compose the academic community of the campus under study. The results demonstrated that in a globalized way, the communication is seen in a way that varies predominantly between regular and good. When the analysis was performed by segments, no distinctions were found capable of justifying specific interventions by groups. The questionnaire also brought a series of reports of communication failures occurring on campus that were used in the formulation of proposals for interventions capable of providing an advance in the condition of the campus communicative process.